Child sexual abuse: observations for clinical practice of social workers with families - de Toro Consuagra, Ximena Leonor (Cuadernos de Trabajo Social, 2021)
This article is a literature review of the latest information regarding the criteria taken into account for interventions with parents without abusive conduct (carers) by social workers involved in clinical practice in the child protection system, and specifically in programmes to support children who have been victims of child sexual abuse. The search emphasised factors aimed at strengthening the therapeutic alliance between social workers and families, which is considered a key element in preventing families from abandoning the process of overcoming abusive experiences. The search for texts was carried out based on keywords in journals specialising in childhood, family and sexual abuse. Seven key dimensions were identified: a) effects of post-disclosure parental support; b) intrapersonal consequences for carers to be taken into account by social workers; c) interpersonal consequences for carers to be taken into account by social workers; d) importance of involving parent; e) importance of first responses from protection system; f) therapeutic process with carers; and g) importance of strengthening parental alliance. The article concludes with general recommendations and future lines of research.